Documenting d/Deaf and Hard of Hearing Children’s Psychosocial Experiences at a School in Harare, Zimbabwe - James Maizere; Loveness Dube (Scientia Publica Media, 2025)
The inclusion of d/Deaf and Hard of Hearing (d/DHH) may not be complete without considering their psychosocial issues. This study documented d/DHH’s psychosocial experiences in inclusive education at a mainstream school. The study employed a qualitative research approach and a narrative research design to guide the research process. The study population comprised all thirty-two mainstream teachers and all four school administrators at the school. Of the thirty-two teachers, ten were purposively sampled to make two Focus Group Discussions (FGDs) of five members each. Besides, two school administrators were also purposively sampled from the selected school to dialogue on their psychosocial experiences in educating d/DHH children. One of the major findings was that d/DHH children had language barriers to communicating with their hearing counterparts. The study also found that d/DHH children faced negative relationships with their hearing peers at the mainstream school, a form of social friction. The study further found that the d/DHH children benefited, psychosocially, from attending various activities with the hearing children. Based on these findings, the study recommended that all Teacher Education Programmes should make it mandatory that the Zimbabwe National Sign Language be an exit skill for all student teachers. The study further recommended that there be guidance and counselling programmes to enable d/DHH and hearing children to understand each other and cooperate.